2012
DOI: 10.1007/s12639-012-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasitic infection in diverse species of domestic ruminants inhabiting tribal rural areas of southern Rajasthan, India

Abstract: A total of 415 adult domesticated ruminants, 130 cattle (Bos taurus), 108 buffaloes (Bubalus bubalis), 94 goats (Capra hircus) and 83 sheep (Ovis aries) inhabiting tribal rural areas of southern Rajasthan, India were investigated for evidence of gastrointestinal protozoan and helminthic infections. In southern Rajasthan humid ecosystem is predominant and has number of perennial freshwater bodies. Fresh faecal samples of these animals were examined microscopically by direct wet smear with saline and 1 % Lugol's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 10 publications
2
30
1
1
Order By: Relevance
“…Hirani et al (2006) reported 44.2 % prevalence of GI parasites in adult cattle in central Gujarat, which is in array with present study conducted in south western part of Gujarat. However, more than 50 % incidence of parasitic infections in cattle and buffaloes has also been recorded from Gujarat (Pethkar and Hiregoudar 1972), Karnataka (Krishnamurthy and D' Souza 2014) and Rajasthan (Choubisa and Jaroli 2013). In this study, the most prevalent GI parasites in cattle and buffaloes were B. sulcata and Eimeria spp.…”
Section: Discussionmentioning
confidence: 50%
“…Hirani et al (2006) reported 44.2 % prevalence of GI parasites in adult cattle in central Gujarat, which is in array with present study conducted in south western part of Gujarat. However, more than 50 % incidence of parasitic infections in cattle and buffaloes has also been recorded from Gujarat (Pethkar and Hiregoudar 1972), Karnataka (Krishnamurthy and D' Souza 2014) and Rajasthan (Choubisa and Jaroli 2013). In this study, the most prevalent GI parasites in cattle and buffaloes were B. sulcata and Eimeria spp.…”
Section: Discussionmentioning
confidence: 50%
“…Hirani et al (2006) reported 44.2 % prevalence of GI parasites in adult cattle in central Gujarat, which is in array with present study conducted in south western part of Gujarat. However, more than 50 % incidence of parasitic infections in cattle and buffaloes has also been recorded from Gujarat (Pethkar and Hiregoudar 1972), Karnataka (Krishnamurthy and D'souza 2014) and Rajasthan (Choubisa and Jaroli 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It plays a crucial role in reducing animal production by lowering the working capacity, growth, body weight and milk yield (Choubisa and Jaroli 2013;Panigrahi et al 2014). In the recent years, various epidemiological surveys of GI parasitic infections in domesticated animals have been carried out in different parts of India (Samanta and Santra 2007;Jyoti et al 2011;Singh et al 2102a;Rahman et al 2012;Krishnamurthy and D'souza 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, cost/ benefit analysis of eradication showed an actual cost of US$ 538 million between 1917 and 1992 (current programs cost approximately US$ 3.5-4.0 million per year [94,305]. Although cattle are the main reservoir of the bacterium, buffaloes are also infected by M. bovis, developing same clinical characteristics [34,306,307]. Buffalo embodies a significant economic activity in many countries such as Brazil where its herd of water buffalo (approximately 3 million animals) is the largest one of the Americas.…”
Section: Emerging Infectious Diseases In Water Buffalo -An Economic Amentioning
confidence: 99%
“…They are mostly raised in rural areas and are great in adapting to various environmental conditions [87]. They also represent a potential zoonotic threat because they can be a source of infection to other animal species and to human beings [34,130,307].…”
Section: Emerging Infectious Diseases In Water Buffalo -An Economic Amentioning
confidence: 99%